Methods of Covid-19 Crisis Management in the International Tourism and Civil Aviation Transport - Jindřich Ploch; Monika Palatková (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
Tourism and air transport are among the sectors most affected by the Covid-19 crisis. The pandemic lasting more than a year is reflected in short-term effects in both sectors, but there are also severe long-term consequences. National authorities will have to set recovery plans following the relevant policies and encompass international cooperation with public and private entities. The article aims to identify the methods and procedures that can be implemented, which can mitigate the consequences of the crisis and initiate the renewal of international tourism and air transport in particular. The paper's methodology is based on current statistical data and strategic documents at the national and international level represented by the international organizations (esp. UNWTO, WTTC, IATA, ICAO, ECAC). The focus is on the crisis management of the public sector entities in terms of the definition and implementation of reconstruction strategies, on private sector stakeholders, on the interconnection of the tourism and the air transport sectors, and cooperation in the international environment. Methods and tools for the renewal of both sectors are based on a strategic approach of the public sector, support for the introduction of new business models in the private sector, change in the product and marketing mix, digitization, innovation, and education.
Keywords: H12; H50; L83; L9; R4; 330; international tourism; international air transportation; tourism policy; transportation policy; crisis management; strategic management